Types of second primary cancer influence overall survival in cutaneous melanoma - Zheng, Guoqiao; Chattopadhyay, Subhayan; Sundquist, Kristina; Sundquist, Jan; Försti, Asta; Hemminki, Akseli; Hemminki, Kari (BMC cancer, 2021)
BACKGROUND: Favorable survival in malignant cutaneous melanoma (melanoma) has increased the likelihood of second primary cancer (SPC). We assess the influence of patient characteristics at diagnosis of first melanoma and the type of SPC (second melanoma and other SPC) on overall survival. METHODS: We used the Swedish Cancer Registry data to assess overall survival in melanoma for the period 1990 to 2015. Kaplan-Meier curves were plotted and hazard ratios (HRs) were estimated with Cox regression models by considering SPC diagnosis as a time-dependent variable. RESULTS: A total of 46,726 patients were diagnosed with melanoma, and 15.3% of them developed SPC, among which, two thirds were other SPCs. Second melanomas were diagnosed early (31% during the first year) compared to non-melanoma SPCs (9.5%). Survival for women with second melanoma or other SPC (56 and 21% alive after 25 years of follow-up, respectively) exceeded the male rates (21 and 10%, respectively) but all these figures were lower than for females (60% alive) or males (48%) without SPC. Time dependent analysis showed vastly increased HRs for cancer types that are fatal also as first cancers, but SPC-specific HRs remained relatively uniform, irrespective of SPC diagnosed soon or late after first melanoma. In early-onset melanoma, SPC diagnosis after 10 years may not negatively influence overall survival. CONCLUSIONS: As the overall survival of patients with many types of SPCs is unfavorable, advice about health lifestyle should benefit smoking patients and early detection methods may be recommended for SPCs of the breast, prostate and colorectum.
Keywords: senioři; proporcionální rizikové modely; Proportional Hazards Models; kouření; senioři nad 80 let; Skin Neoplasms; Melanoma; Time Factors; sexuální faktory; Kaplan-Meier Estimate; Middle Aged; registrace; mužské pohlaví; Kaplanův-Meierův odhad; Sweden; Registries; věkové faktory; Aged, 80 and over; Smoking; ženské pohlaví; přežívající onkologičtí pacienti; melanom; Humans; sekundární malignity; nádory kůže; Sex Factors; Cancer Survivors; časové faktory; lidé středního věku; Age Factors; Švédsko; Female; Aged; lidé; Male; Neoplasms, Second Primary